STUDY ON EFFECT OF DIFFERENT PACKAGING MATERIALS AND SHELF LIFE ON THE CHEMICAL QUALITY OF CROSSBRED LANDRACE PORK - I P. E., Widiana; Sriyani, N L. P; Putri, T. I. (Jurnal Peternakan Tropika, 2020)
This research was aimed at determining the effect of different wrapping materials on shelf life and the chemical quality of crossbred landrace pork. The research was based on a 2 x 3 factorial design in a completely randomized design (CRD) of (2 levels of wrapping materials and 3 levels of storage period). The treatment of wrapping materials were plastic and teak leaf. The treatments of storage period were pork wrapped and stored at 4 hours (T4), 8 hours (T8) and 12 hours (T12). Data was analyzed using analysis of variance (ANOVA) and the treatments that had significant effects were further analyses using the Duncan test. The results showed that there were an interaction between different materials and shelf life which affected the protein content of crossbred landrace pork in 12 hours of storage. The different materials had no effect on the chemical content of crossbred landrace pork at 4  and 8 hours storage, but had a significant effect (P <0.05) on the 12 hours storage time. The difference in storage time had a significant effect (P <0.05) on the moisture content and protein content of crossbred landrace pork. The conclusion of this research is there were an interaction between different materials and shelf life which affected the protein content of crossbred landrace pork in 12 hours of storage. There were no chemical content effect to crossbred landrace pork when it wrap by plastic or teak leaf which saved for 4 hours and 8 hours, but its effected for crossbred landrace pork which saved for 12 hours, meat’s protein content is higher when its wraped by teak leaf than wrapped by plastic. Both of wrapped material was effected to water and protein content of the cross landrace pork. Keywords: pork, wrapping materials, shelf life.